2019
DOI: 10.1210/js.2019-00041
|View full text |Cite
|
Sign up to set email alerts
|

MKRN3 Mutations in Central Precocious Puberty: A Systematic Review and Meta-Analysis

Abstract: MKRN3 mutations represent the most common genetic cause of central precocious puberty (CPP) but associations between genotype and clinical features have not been extensively explored. This systematic review and meta-analysis investigated genotype-phenotype associations and prevalence of MKRN3 mutations in CPP. The search was conducted in seven electronic databases (Cochrane, EMBASE, LILACS, LIVIVO, PubMed, Scopus, and Web of Science) for articles published until 4 September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
73
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 47 publications
7
73
0
12
Order By: Relevance
“…In this study, the mean CA of pubertal onset was similar in patients with CPP due to MKRN3 mutations and in those with idiopathic CPP, confirming the data reported previously [31,32]. In contrast with our data, Simon et al [6] demonstrated that girls with CPP due to MKRN3 mutation were younger at puberty onset than those without MKRN3 mutation [6].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, the mean CA of pubertal onset was similar in patients with CPP due to MKRN3 mutations and in those with idiopathic CPP, confirming the data reported previously [31,32]. In contrast with our data, Simon et al [6] demonstrated that girls with CPP due to MKRN3 mutation were younger at puberty onset than those without MKRN3 mutation [6].…”
Section: Discussionsupporting
confidence: 91%
“…The longitudinal analysis of categorical BMI in both groups revealed similar evolution. This information was lacking in previous studies on MKRN3 mutations [32].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations